2007
DOI: 10.1111/j.1469-7610.2007.01736.x
|View full text |Cite
|
Sign up to set email alerts
|

Genomic imprinting and the expression of affect in Angelman syndrome: what's in the smile?

Abstract: Background. Kinship theory (or the genomic conflict hypothesis) proposes that the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
67
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 28 publications
6
67
0
1
Order By: Relevance
“…In contrast to children with Prader-Willi syndrome, Angelman syndrome children are highly active, with reduced duration of sleep, frequent suckling attempts, and enhanced levels of socially-directed positive affect (Cohen et al, 2005;Oliver et al 2007). These diverse phenotypes have been interpreted as reflecting increased behavioral and energetic demands on the mother, as predicted by the direction of imprinted-gene deviation, towards reduced relative effects from the maternallyexpressed imprinted gene UBE3A (Oliver et al 2007).…”
Section: Angelman Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to children with Prader-Willi syndrome, Angelman syndrome children are highly active, with reduced duration of sleep, frequent suckling attempts, and enhanced levels of socially-directed positive affect (Cohen et al, 2005;Oliver et al 2007). These diverse phenotypes have been interpreted as reflecting increased behavioral and energetic demands on the mother, as predicted by the direction of imprinted-gene deviation, towards reduced relative effects from the maternallyexpressed imprinted gene UBE3A (Oliver et al 2007).…”
Section: Angelman Syndromementioning
confidence: 99%
“…These diverse phenotypes have been interpreted as reflecting increased behavioral and energetic demands on the mother, as predicted by the direction of imprinted-gene deviation, towards reduced relative effects from the maternallyexpressed imprinted gene UBE3A (Oliver et al 2007). Such an increased 'set-level' of demands imposed on mothers might be expected to lead to insecure forms of attachment, unless the demands are met, whereupon social-emotional development should proceed as normally as possible under the circumstances of severe intellectual disability that characterize this syndrome.…”
Section: Angelman Syndromementioning
confidence: 99%
“…Through this they identified that higher levels of laughing and smiling behaviors occurred when adult attention, and particularly adult eye contact, was present. Finally, employing sequential lag analyses to naturalistic observation data, Oliver et al (2007) found that every smile by children with Angelman syndrome (n=13) evoked higher levels of eye contact, smiles and attention from the adult than smiles of children without Angelman syndrome (matched for degree of intellectual disability). This social contact then makes the child smile; possibly as a result of the positive affect and internal reward mechanisms initiated by these interactions (Oliver et al, 2007).…”
mentioning
confidence: 99%
“…Finally, employing sequential lag analyses to naturalistic observation data, Oliver et al (2007) found that every smile by children with Angelman syndrome (n=13) evoked higher levels of eye contact, smiles and attention from the adult than smiles of children without Angelman syndrome (matched for degree of intellectual disability). This social contact then makes the child smile; possibly as a result of the positive affect and internal reward mechanisms initiated by these interactions (Oliver et al, 2007). Adams et al (in press) extended the work of Horsler & Oliver (2006b), investigating the effect of age on smiling and laughing, looking and approach behaviours demonstrated by children with Angelman syndrome.…”
mentioning
confidence: 99%
“…During early childhood, individuals with Angelman syndrome show excessive degrees of solicitation to parents, as implicated by extreme levels of crying, hyperactivity and sleeplessness; they also, however, show high levels of positive mood, notably in social interactions [136,137]. Taken together, these traits have been interpreted as essentially the psychological opposite of Prader-Willi syndrome, whereby increased paternal imprinted-gene influences favour increased solicitation via activity and positive mood.…”
Section: (F ) Social Interactions With Kin Early In Life Generate Andmentioning
confidence: 99%